HUBUNGAN PERTUMBUHAN ASSET, KONTRIBUSI BRUTO, KLAIM DAN INVESTASI TERHADAP EFISIENSI PERUSAHAAN ASURANSI SYARIAH - NUR - HAJIJAH; Ahmad Junaidi; Nadila Deryza Syofrin; Mariyam Mariyam (Program Studi Ekonomi Syariah IAI Muhammadiyah Bima, 2025)
Business efficiency proves the ability of its managerial in facing intense competition, especially those of sharia insurance companies. The purpose of this study was to examine the relationship between growth assets, gross contributions, claims and investment to the efficiency of sharia insurance company in 2016-2019. This study used DEA analysis (Data Envelopment Analysis) to measure the efficiency level of seven sharia insurance companies in 2016 to 2019 by using input variables (asset totals, claim payments) and output variable (revenues and tabarru’ funds), then examine the relationship of independent variables (growth assets, gross contributions, claims and investment) against dependent variable (the efficiency of sharia insurance company) by using multiple linear regression analysis. The results of the study demonstrated that the seven companies experienced the efficiency level of 100% in 2016 to 2017, but in 2018 to 2019 the three sharia insurance companies (PT Asuransi Jiwa Syariah Al-Amin, PT Asuransi Jiwa Syariah Jasa Mitra Abadi and PT Reasuransi Syariah Indonesia; or PT ReINDO Syariah) experienced an inefficiency. Then the relationship of growth assets, gross contributions, claims and investment to the efficiency of sharia insurance company does partially not effect significantly, but does simultaneously effect significantly. Keywords: Growth Assets, Gross Contributions, Claims, Investment, Efficiency of Sharia Insurance Company; DEA